Introduction to group therapy : a practical guide - Fehr, Scott Simon (Advances in psychology and mental health, 2003)
Introduction to Group Therapy: A Practical Guide, Second Edition expands on issues presented in the book's first edition and introduces new information on topics such as the historical beginnings of group therapy, theories, modalities, practical issues of how to set up an office for an effective group environment, surviving your training sites, problem clients, contemporary issues drawn from online discussion, and developing a group practice. The book also includes case studies, review questions, a glossary, appendices of relevant topics, and an extensive bibliography.